Evaluate the Reason and Overall Satisfaction of Consumers to Buying Health Insurance Products - Vasani Sureshbhai Vithalbhai (Journal La Bisecoman, 2022)
The current study (article) investigated why people purchase health insurance products and why they do not, as well as how satisfied consumers are with insurance products overall following claim settlement. A systematic questionnaire was used to gather data from 140 respondents, and reliability tests, cross-tabulation, the Mann-Whitney U test, the Kruskal-Wallis test, weighted average means, and percentage analysis were employed. The study's key finding suggested that one motivation is to safeguard against the rising cost of healthcare, while lack of awareness is the cause of not purchasing it. The null hypothesis is fail-to-reject, indicating that there is no discernible difference between the means of overall service satisfaction with respect to demographic factors and the 77.2% of respondents who are satisfied with their health insurance policy.